2019
DOI: 10.1096/fj.201902396r
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary manganese on experimental colitis in mice

Abstract: Diet plays a significant role in the pathogenesis of inflammatory bowel disease (IBD). A recent epidemiological study has shown an inverse relationship between nutritional manganese (Mn) status and IBD patients. Mn is an essential micronutrient required for normal cell function and physiological processes. To date, the roles of Mn in intestinal homeostasis remain unknown and the contribution of Mn to IBD has yet to be explored. Here, we provide evidence that Mn is critical for the maintenance of the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
5
42
0
Order By: Relevance
“…Consistent with our finding that Mn deficiency is sufficient to disrupt intestinal barrier function (Fig. 3), an Mn-deficient diet renders mice susceptible to epithelial injury in the DSS model, which is characterized by increased inflammatory cytokines and exacerbated histopathology in the colon (45).…”
Section: The Development Of Mature Isolated Lymphoid Follicles Driven Bysupporting
confidence: 91%
“…Consistent with our finding that Mn deficiency is sufficient to disrupt intestinal barrier function (Fig. 3), an Mn-deficient diet renders mice susceptible to epithelial injury in the DSS model, which is characterized by increased inflammatory cytokines and exacerbated histopathology in the colon (45).…”
Section: The Development Of Mature Isolated Lymphoid Follicles Driven Bysupporting
confidence: 91%
“…A similar result has also been reported where Mn markedly increased the production of inflammatory cytokines and chemokines in human monocyte-derived macrophages [18]. However, Choi and colleagues reported that a diet with adequate Mn notably depressed the expression of inflammatory cytokines TNF-α, IL-6, IL-1β, and IL-10 when compared to the Mn-deficient diet in colon mucosa of DSS-treated mice [42]. Excess Mn exposure was also reported to inhibit or induce the expression of genes of proinflammatory cytokines in chickens [19,41], indicating that dietary Mn modifies inflammatory cytokines in a dose-dependent manner and/or is dependent on the experimental model.…”
Section: Discussionsupporting
confidence: 75%
“…These results are congruent with previous outcomes in mice and indicate that Mn is necessary for proper maintenance of the intestinal barrier. For example, Mn provided protection against dextran sulfate sodium (DSS)-induced colon injury [42]. It was postulated that the positive effect of Mn on the intestinal barrier was mediated by MnSOD [23], which is in agreement with the efficacious protection of the small intestine from ionizing radiation damage through overexpression of MnSOD in mice [43].…”
Section: Discussionmentioning
confidence: 80%
“…Both the heterozygous and homozygous Zip8 393T-KI male mice exhibited a more severe phenotype than WT mice. We note a recent report of enhanced susceptibility to DSS-induced injury in mice fed Mn-deficient chow ( 45 ). We acknowledge that our experiments do not directly test that abnormal Mn homeostasis specifically drives the colitis phenotype, and future experiments will test variable Mn dietary content.…”
Section: Discussionmentioning
confidence: 73%